Furniture design education with 3D printing technology - KOÇ SAĞLAM, CEREN (Springer, London/Berlin, 2021)
Three-dimensional printing technology has an important place in furniture and interior design, a strong global sector that responds rapidly to the changing needs and expectations of the individual and society. The main objective of design education should be to equip us to imagine new models of life. Among the most attractive benefits of 3D printing technology that make it a boon to designers working in the building and furniture sector are that it enables them to seek original forms that cannot be produced in molds, it generates less waste, and is accessible to all. Today, innovation in the profession, innovative materials, and knowledge of innovative production technologies that feed creative thinking have become ever important features of design education. This knowledge will allow us to imagine, discuss and pioneer design production ideas for new life models. This paper discusses 3D printing technology, the furniture design studio method and its contribution to design education in the Production Techniques courses of the Interior Architecture Department of Marmara University’s Faculty of Fine Arts led by Professor Meltem Eti Proto, Instructor Can Onart, Lecturer T. Emre Eke, and Research Assistant Ceren Koç Sağlam.
Keywords: Sosyal ve Beşeri Bilimler; Sanat; İç Mimarlık; Sanat ve Tasarım; Tasarım Çalışmaları; Social Sciences and Humanities; Art; Interior Architecture; Art and Design; Design Studies; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; SANAT; MİMARİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ART; ARCHITECTURE; Mimari; Görsel Sanatlar ve Gösteri Sanatları; Müzecilik; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Architecture; Visual Arts and Performing Arts; Museology; Physical Sciences; Social Sciences & Humanities